(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2018)
This paper proposes an analysis of the meaning of the two recurring dreams of Dora, Freud’s famous patient, from the perspective of Medard Boss’s daseinanalysis of dreams. As far as the author is aware, this is the first existential-phenomenological analysis of the dreams of Freud’s patient.